Pengembangan Video Animasi Berbasis Kearifan Lokal pada Pembelajaran IPA Kelas V di Sekolah Dasar - Aprizal Lukman; Dwi Kurnia Hayati; Nasrul Hakim (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to develop a video animation of science learning materials on water recycling and natural events. The development model used is the DDD-E model. The product developed wasvalidated by the material validator and the media validator, two and three times, respectively. Thenthe product is revised according to the suggestions and validator input. The final validation resultsindicate the product is worth testing with an average score of 4.6 which is included in the highlyvalid criteria. After that, an animated video product is tested on elementary school students to findout the practicality of the media